The beginnings of obstetrics as a medical specialty in Peru - Deza Bringas, Luis (2015)
The birth of Obstetrics and specialty in Peru and evolution are linked, like all great human work, to the action of paradogmáticas people and socio-economic circumstances surrounding its development